2014
DOI: 10.5792/ksrr.2014.26.4.253
|View full text |Cite
|
Sign up to set email alerts
|

Baker's Cyst Filled with Hematoma at the Lower Calf

Abstract: Baker's cyst is a distension of the gastrocnemius-semimembranosus bursa of the knee, which communicates with the posterior portion of the joint capsule. Baker's cyst is commonly located in the inferomedial or superficial layers of the knee joint and rarely extends laterally or proximally. Complications of Baker's cysts are dissection, rupture, pseudothrombophlebitis, leg ischemia, nerve entrapment, and compartment syndrome. However, hematomas in the Baker's cyst have not been reported in Korea. We report a rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…However, MRI provides detailed information with a better demonstration of fluid within calf fascia. [189]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, MRI provides detailed information with a better demonstration of fluid within calf fascia. [189]…”
Section: Discussionmentioning
confidence: 99%
“…Baker's cyst is a distention or enlargement of the gastrocnemius-semimembranosus bursa (GSB) toward popliteal fossa. [1] Communication through a capsular opening between the knee joint cavity and GSB is a common anatomic variant in a normal joint [Figure 1]. Handy reported that Baker's cyst may be found in 5%–32% of symptomatic knees in a review article.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popliteal cyst in this case showed low signal intensity on T1-weighted images and heterogeneous intermediate signal intensity on T2-weighted images. Thus far, pigmented villonodular synovitis, hematoma, and infection have been reported in cases of popliteal cyst with unusual appearance on MRI [6, 7]. Unless the connection between the cyst and the subgastrocnemius bursa can be identified on MRI, malignant tumour, aneurysm, or benign solid tumour should be considered [8].…”
Section: Discussionmentioning
confidence: 99%
“…Unless the connection between the cyst and the subgastrocnemius bursa can be identified on MRI, malignant tumour, aneurysm, or benign solid tumour should be considered [8]. In all previous cases with unusual signal intensities inside the popliteal cyst, open resection was performed for diagnosis and treatment [6, 7]. The unusual presentation of the popliteal cyst on preoperative MRI was due to necrotic synovial villi inside the cyst.…”
Section: Discussionmentioning
confidence: 99%